Role of Dendritic Epidermal T Cells in Cutaneous Carcinoma - Xiang, Jian; Qiu, Minghui; Zhang, Hongyi (Frontiers in Immunology, 2020)
Dendritic epidermal T cells (DETCs) are γδ T cells expressing invariant Vγ5Vδ1 T cell receptor (TCR) in murine epidermis. The generation, development and maturation of DETC progenitors are in the fetal thymus depending on skint-1, TCR and cytokines. Then DETC progenitors migrate to the epidermis guided by selections, CCR10, CCR4 etc. Eventually mature DETCs proliferate and maintain a homeostatic population in the epidermis through of IL-15 and AHR signaling. Once the skin is damaged or tumorigenesis, DETCs are activated and responsible by producing multiple cytokines. In cutaneous carcinoma, DETCs generally inhibit tumor development directly in non- major histocompability complex (MHC) restricted manner with the assistance of cytokines. DETCs also recognize and inhibit tumor via TCR, non TCR receptors (such as 2B4, NKG2D) or both. However, DETCs may promote tumor progression in certain microenvironment. This study summarizes the biogenesis and function of DETCs in cutaneous carcinoma, and helps develop DETCs based anti-tumor immune therapeutics.